Building noble morals through worship: a study from Buya Yahya and Ustadz Adi Hidayat - Satra, Alihan; Ramadhan, Rahmad; Nazhifah, Nazhifah; Rahmadani, Novi (At- Ta'lim : Jurnal Pendidikan, 2025)
The paper "Building Noble Morals Through Worship: A Study of Buya Yahya and Ustadz Adi Hidayat" investigates the connection between moral growth in modern society and worship. The significance of worship in forming moral character and personality is emphasized in this article. This study examines how worship can promote high morals through literature reviews and video analysis of the two scholars' teachings. The main findings show that sincere worship leads to positive moral behavior, and both scholars emphasize the importance of preparation and intention in worship. The study comes to the conclusion that raising the standard of worship is crucial for moral growth and promotes more research into how worship shapes character. There is also discussion of limitations and suggestions for further study.